Evaluation of the cost saving potential of introducing Benepali® and Flixabi® on the European and Italian markets - Negrini, Cristina; Psachoulia, Emi (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
INTRODUCTION: Biosimilar products play an important role in improving the access to biological medicines for an increased number of patients and enhancing the financial sustainability of the health systems. AIM: To assess the cost saving potential associated with the introduction of two biosimilars (Benepali® and Flixabi®) vs. their respective reference biological products on the European and Italian markets. METHODS: A budget impact model was developed to estimate the cost saving of the hypothetical introduction of Benepali® and Flixabi® vs. Enbrel® and Remicade®, respectively, in three European countries. The analysis was conducted from the payer perspective, over a 3-year period. In addition, the same model was used to assess the impact of Benepali® vs. Enbrel® in three Italian regions over a 2-year period. The model compares the costs associated with the current treatment patterns, used to manage patients with all the conditions which Benepali® and Flixabi® are authorized for, with that of a hypothetical treatment pattern in which biosimilar products have been introduced. Only direct costs associated with the drug acquisition were considered. The model was constructed using published country- or region-specific data, where available. Annual drug acquisition costs were calculated using the dosing information from SPCs and country-/region-specific price lists. RESULTS: The introduction of Benepali® and Flixabi® in the biologic therapeutic setting of three European countries resulted in substantial cost savings across the entire scenario, with different penetration over a 3-year period. Similarly, over a 2-year horizon, the introduction of Benepali® in the biologic therapeutic setting of three Italian regions resulted in significant cost savings. In all cases, the greater savings were observed in the scenario where the biosimilars’ penetration was higher. CONCLUSIONS: The introduction of Benepali® and Flixabi® has a substantial cost saving potential for the Italian and European health systems, and the budget impact is sensitive to the uptake rates of the biosimilars market.